The Contribution of Charged Bosons with Right-Handed Neutrinos to the Muon g − 2 Anomaly in the Twin Higgs Models - Guo-Li Liu; Ping Zhou (Universe, 2022)
We examine the charged boson and right-handed neutrino contribution to the muon <semantics>g−2</semantics> anomaly in twin Higgs models with joint constraints of Higgs global fit data, precision electroweak data, leptonic flavor-changing decay <semantics>μ→eγ</semantics>, and the mass requirement of heavy-gauge bosons. It comes with the conclusion that some parameters, such as the coupling of charged Higgs to the lepton <semantics>yμ</semantics>, the top Yukawa <semantics>yt</semantics>, and heavy-gauge boson coupling to the lepton <semantics>Vμ</semantics> are constrained roughly in the range of <semantics>0.12≲yμ≲0.4</semantics>, <semantics>0.4≲yt≲0.9</semantics>, and <semantics>0.47≲Vμ≲1</semantics>, respectively.